Ali Al- Wardi : A Position of Intellectual - Saleh, . Dr. Ali Hakim (Thi Qar Arts Journal, 2025)
This article concerns with the Iraqi prominent sociologist Ali Al-Wardi (1913-1995), as an intellectual occupied a unique position in Iraqi culture in the second half of the twentieth century. In order to comprehend this position, the article describes the Iraqi political and cultural conditions in which al-Wardi’s writings emerged and the circumstances of the emergence of sociology as a scientific branch in the Iraqi academy. The article focuses on the role that Al-Wardi attributed to knowledge as a major component and a guide for public policy, and then it evaluates and criticizes his theses and their realistic and scientific efficiency to play this role.